Understanding Perak as a travel destination: Domestic tourists’ behaviour and travel choice / Anesha Humaira Abu Hasan, Haleesya Abu Bakar and Sarah Ahmad Razlah - Abu Hasan, Anesha Humaira; Abu Bakar, Haleesya; Ahmad Razlah, Sarah (2021)
Identifying tourist most preferred travel destination based on travel criteria offers the ability to properly promote a travel destination. This can beneﬁt Tourism Perak Malaysia to further understand and make the appropriate promoting strategies. The objectives of this study are to determine the travel behaviour of domestic tourists in visiting Perak, to determine the relative importance of travel criteria for selecting Pulau Pangkor, Ipoh, and Kuala Kangsar as travel destinations and to determine the most preferred travel destination based on tourist criteria. In this research, data were obtained from 219 respondents through a survey. Descriptive analysis and Analytical Hierarchy Process (AHP) were employed for analysis. Analytical Hierarchy Process (AHP) is an effective Multi-Criteria Decision-Making Method (MCDM) which provides a rank of travel criteria for the selection of travel destination. Although it is commonly used for ranking individual preference, the technique can be extended for group decision making. The AHP decision problem was structured into a three-level hierarchy with four criteria involved in the selection of travel destination; beauty, cost, transportation and accommodation. The results showed that among the four travel criteria selected, the most important criterion in selecting a travel destination is beauty followed by cost, accommodation and transportation. Meanwhile in every criteria, Ipoh was rated at the highest rank by respondents. Overall, Ipoh is recommended as the most preferred travel destination in Perak followed by Pulau Pangkor and Kuala Kangsar. In addition, information of demographic characteristics and tourists’ behaviour helps in tourist analysis.